Family size and maternal health: evidence from the One-Child policy in China - Wu, Xiaoyu; *Li, Lixing (Journal of Population Economics, 2012)
In this paper, we examine the impact of family size on maternal health outcomes by exploiting the tremendous change in family size under the One-Child policy in China. Using data from the China Health and Nutrition Survey 1993-2006, we find that mothers with fewer children have a higher calorie intake and a lower probability of being underweight and having low blood pressure; meanwhile, they have a higher probability of being overweight. This would occur if a smaller family size increases the food consumption of mothers, leading underweight women to attain a normal weight and normal weight women becoming overweight. Robust tests are performed to provide evidence on the hypothesis that the tradeoff between children's quantity and mother's "quality" is through a budget constraint mechanism, that is, having more children decreases the resource allocated to mothers and affects their health outcomes.
Keywords: Maternal health; Quantity-quality tradeoff; One-Child policy